Emerging Foundations for International Responsibility for Natural Disasters Resulting from Climate Change - AbdKader, Raneen; AlMaliki, Hadi (Journal of Legal Sciences, 2026)
With the emergence of many methods whose use is exceptionally dangerous despite being legitimate acts not prohibited by international law, they cause serious damage as a result of this danger. When legal thought finds that the application of the traditional theories will inevitably prevent the development targeted by States and the progress of States' technical and industrial progress. The search for foundations has begun more in line with the requirements of contemporary reality, By creating a legal basis for international responsibility that achieves a greater proportion of justice in society, objective responsibility has emerged as an evolving stage of international responsibility in law International, after the emergence of many risks resulting from natural behaviors of states such as air aviation accidents and marine disasters as a result of energy extraction and minerals, and accidents resulting from the use of nuclear energy. The International Law Commission had launched the designation of international liability for injurious consequences arising out of acts not attended by international law, perhaps the most common of which was the theory of risk.